2016
DOI: 10.1080/15374416.2016.1169537
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Relations Between Temperament and Parenting Predicting Preschool-Age Children’s Adjustment

Abstract: Objective: Bidirectional associations between child temperament (fear, frustration, positive affect, effortful control) and parenting behaviors (warmth, negativity, limit setting, scaffolding, responsiveness) were examined as predictors of preschool-age children’s adjustment problems and social competence. Method: Participants were a community sample of children (N = 306; 50% female; 64% European American) and their mothers. Observational measures of child temperament and parenting were obtained using labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 65 publications
3
39
0
Order By: Relevance
“…This suggests that dyads with contingent parents and successful children were engaged in a form of positive feedback loop where contingent interventions led to child success, and child success then led back to contingent interventions. This reflects the reciprocal, intrinsically intersubjective nature of scaffolding (Salonen et al 2007), and is consistent with the recent findings of Klein et al (2016) who identified a bidirectional relationship in preschool dyadic interaction whereby maternal behaviour influences child development and vice versa. The presence of such dyadic feedback loops represents both a challenge and an opportunity for intervention science: the challenge comes from the fact that positive developmental feedback loops mean that more capable children are more able to elicit and internalise effective parental intervention, and so become yet more capable, whereas at-risk children struggle to elicit or benefit from the kind of parental intervention which could improve their developmental outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that dyads with contingent parents and successful children were engaged in a form of positive feedback loop where contingent interventions led to child success, and child success then led back to contingent interventions. This reflects the reciprocal, intrinsically intersubjective nature of scaffolding (Salonen et al 2007), and is consistent with the recent findings of Klein et al (2016) who identified a bidirectional relationship in preschool dyadic interaction whereby maternal behaviour influences child development and vice versa. The presence of such dyadic feedback loops represents both a challenge and an opportunity for intervention science: the challenge comes from the fact that positive developmental feedback loops mean that more capable children are more able to elicit and internalise effective parental intervention, and so become yet more capable, whereas at-risk children struggle to elicit or benefit from the kind of parental intervention which could improve their developmental outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…The second aim of this study was to test the mediating effects of children’s temperament between mothers’ parenting and children’s aggression from the mothers’ perspective. Previous research has consistently confirmed that parental behaviors can shape children’s temperament and emotional and self-regulatory characteristics, which in turn affect children’s adjustment [ 10 , 13 , 24 ]. Specifically, maternal discipline and communication seem to facilitate children’s positive emotions, discourage negative affects and develop effective emotional regulation [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Child temperament and parental socialization have been established as potential mechanisms that contribute to behavioral problems [ 5 , 6 ]. Both temperament and parenting not only seem to contribute uniquely and simultaneously to children’s behavioral and emotional adjustment, but they can also both affect each other in a bidirectional process that may contribute to exacerbating or inhibiting behavioral problems [ 7 , 8 , 9 , 10 ]. Parents can shape children’s temperament and emotional and self-regulatory characteristics, which in turn are key predictors of children’s adjustment [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, individual differences in child temperament also appear to influence parental behaviors (Klein et al 2016). Such effects have been documented in very young children and have also shown to have lasting effects across development, which then serve to further exacerbate (or perhaps attenuate) youth behavioral and emotional problems (Barnett and Scaramella 2015).…”
Section: Discussionmentioning
confidence: 99%